On the Possibility and Impossibility of Modernist Cinema: Péter Forgács’ Own Death - van Alphen, Ernst (Filozofski vestnik, 2016)
Whereas Modernism is a productive notion in literary studies and art history for the understanding of twentieth century cultural practices, in cinema studies it is hardly viable. The unique position of cinema is not only caused by a different history, but also by its medium specificity. But it is not clear at all how the medium specificity of Cinema can be imagined or defined. If it is the “task” of 20th century Modernism to purify media of eve- rything that is not specific to the medium, it implies that cinema cannot be considered an art medium. To counter this notion of Modernism in terms of medium the idea will be defended that the specificity of cinema resides in its synthetic nature, that is, in its impurity. Next, I explore a Modernist attempt in cinema, adopting a device that is usually seen as specific for the literary text, in the sense that only in textual form the device is really possible and effective. I will examine Own Death, made in 2007 by Hungarian artist and filmmaker Péter Forgács, based upon the 2002 novella of the same name by Hungarian author Péter Nádas. The Modernist device that is consistently used in Nadas’ novella device is the one of consistent character-bound focalization. The story told is from begin- ning to end presented through the eyes and experience of one focalizing subject: a mid- dle aged man in Budapest, who does not feel well and who seems to get a heart attack. I call the device “radical perspectivism,” and it concerns a radical, that is, systematic, consistent adaptation of one point of view, or better, one focalizing position.